PENERAPAN MODEL PEMBELAJARAN KOLABORATIF TEKNIK BUZZ GROUP UNTUK MENINGKATKAN SIKAP DISIPLIN DAN PRESTASI BELAJAR PENDIDIKAN KEWARGANEGARAAN MATERI GLOBALISASI - Mutiarani, Maulida (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
Students’ discipline attitude and learning achievement of civic education in the fourth grade of SD Negeri Ledug was considered low and several students were slow in doing the assignment given by the teachers because they could not optimize the given time well. Their civic education learning achievement often did not reach minimum requirement mastery set by school especially in the topic of globalization. Therefore, this research aimed to develop discipline and civic education learning achievement on materials of globalization through Buzz Group collaborative technique learning model. The subject of this research was Classroom Action Research conducted in two cycles. Each cycle consisted of two meeting and the procedures covering planning, action, observation, and reflection. Data of students discipline development were obtained from students discipline attitude scale and learning achievement data were obtained from the evaluation test given in each meeting. Based on the result, the result of students discipline development in cycle I obtained an average score of 76,61% and improved in cycle II to 83,89%. The obtained average score of learning achievement in cycle I was 63,33% and improved in cycle II to 80%. Therefore it could be concluded that Buzz Group collaborative technique learning model could improve discipline and civic education learning achievement of the fourth graders of SD Negeri Ledug.